Thromboembolic Complications Associated with the Use of Prothrombin Complex and Factor IX Concentrates - Köhler, Michael; Hellstern, Peter; Lechler, Eckhard; Überfuhr, Peter; Müller-Berghaus, Gert (Thrombosis and Haemostasis, 1998)
In 1994, shortly after a heat-treated prothrombin complex concentrate (PCC) had been withdrawn from the German market due to transmission of hepatitis B, the license of another brand was withdrawn, due to 3 acute fatalities associated with the use of this product. We report on the clinical data of altogether 5 patients, who died during a 3 month period in Germany after having received this brand of PCC. All patients had surgery, acquired deficiencies of coagulation factors, and underlying diseases predisposing for thrombosis or disseminated intravascular coagulation. PCC was administered for the prevention of bleeding. In three patients, a drug interaction of PCC with aprotinin may also have played a role. Several points, however, are suspicious of a major causative effect of the respective product, (a) the close temporal correlation between administration of the drug and the subsequent clinical as well as laboratory deterioration, (b) the accumulation of these adverse events in a short period of time, when the use and market share of this brand increased due to the shortage of other products, and (c) laboratory abnormalities of this brand which have been consistently observed in several in vitro studies.